Avaliação dos resíduos sólidos gerados no Restaurante Universitário da UNESP de Rio Claro: uma análise do potencial de compostagem - Picciafuoco, Beatriz Di Francesco [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
A consequence of population growth is the increased generation of solid waste, which requires environmentally and economically viable suitable disposal sites. The scarcity of such sites makes necessary to adopt non-generation measures, reduction, reuse , recycling and treatment of solid waste before final disposal of waste. This paper presents the quantification and qualification of organic waste generated in each sector of the University Restaurant (UR) , by proposing indicators of waste generation per meal (index of waste) . Then, from the characterization of the waste management practices adopted internally, evaluates the potential deployment of the composting process for organic waste, with signaling for opportunities to improve waste management. The diagnosis of waste generation was made based on data collected during the period of 10 days. The waste were classified into 3 groups (organic, recyclable and waste) in each sector of the restaurant ( pre preparation , kitchen and tray return) . The results reveal that 33 % of the waste generated in the UR currently has the potential to be composted in a suitable place on campus. Every meal served generat approximately 124g of waste, of which 35g are organic waste of the pre preparation sector, 49g are remnants of food in the tray’s return and 40g are other kinds of waste, including recyclable and non recyclable. You can still get a higher percentage of compostable if the trays pre-wash is not performed with detergent and water. To minimize the generation of waste trays can be replaced by plates and skimmers and ladles can be replaced by smaller ones. The food exposed in the counter but not consumed, can be distributed to students after the restaurant is closed so this material would not be disposed in the garbage

Uma conseqüência do crescimento populacional é o aumento da geração de resíduos sólidos, o que demanda locais de disposição ambientalmente adequados e economicamente viáveis. A escassez de tais locais faz necessária a adoção de medidas de não geração, redução, reutilização, reciclagem e tratamento dos resíduos sólidos antes de sua disposição final ambientalmente adequada dos rejeitos. O presente trabalho apresenta a quantificação e a qualificação dos resíduos orgânicos gerados em cada setor do Restaurante Universitário (RU) da Universidade Estadual Paulista (UNESP) de Rio Claro, por meio da proposição de indicadores de geração de resíduos por refeição servida (índice de desperdício). Em seguida, a partir da caracterização das práticas de gestão dos resíduos adotadas internamente, avalia o potencial da implantação do processo de compostagem para resíduos orgânicos, com a sinalização para oportunidades de melhoria do manejo dos resíduos. O diagnóstico de geração de resíduos foi realizado com dados coletados diariamente durante o período de 10 dias. Os resíduos foram classificados em 3 grupos (matéria orgânica, reciclável e rejeito) em cada setor do restaurante (pré preparo, cozinha e devolução). Os resíduos gerados pelo serviço de jardinagem do campus também foram analizados para compor o material a ser compostado. Os resultados revelam que 33% dos resíduos gerado no RU atualmente tem potencial para ser compostado. Sendo que a cada refeição servida são gerados aproximadamente 124g de resíduos, dos quais 35g são resíduo orgânico do pré preparo, 49g são restos de alimento na devolução das bandejas e 40g são outros tipos de resíduos incluindo recicláveis e não recicláveis. Para diminuir a geração de resíduos as bandejas podem ser substituídas por pratos e as conchas/escumadeiras trocadas por utensílios de menor tamanho...
Keywords: Universidade Estadual Paulista Júlio de Mesquita Filho; Resíduos; Resíduos sólidos; Restaurantes, bares, etc - Rio Claro (SP); Residuos organicos; Adubos compostos